Environmental effects on transport properties of PdSe2 field effect transistors. (2020) - Giubileo, Filippo; Grillo, Alessandro; Iemmo, Laura; Luongo, Giuseppe; Urban, Francesca; Passacantando, Maurizio; Di Bartolomeo, Antonio
Abstract: We study the effect of pressure, voltage sweeping rate and electron irradiation on the transfer characteristics of field effect transistors fabricated by using exfoliated palladium diselenide flake as transistor channel and Ti/Au metallic electrodes as source and drain. The silicon substrate is used as gate, the flake being transferred on Si/SiO2 substrate. We report ambipolar behavior for the devices under investigation and we demonstrate that external stimuli have dramatic effects on the transport properties. In particular, increasing the acquisition time (by using slower sweeping rate) we demonstrate that the hysteresis observed in the transfer characteristics is widened. Electron irradiation, necessary for SEM imaging of the device, also dramatically affects the characteristics due to induced defects and consequent charge trapping at PdSe2 and SiO2 . Finally, we demonstrate that the device can be tuned from n-type conduction in vacuum, to p-type conduction in atmospheric pressure.